CREATING COMMON PROSPERITY: ECONOMIC EMPOWERMENT POLICY FOR ALL - Bayu Wijokongko; Erwin; Sulaiman (Adisam Publisher, 2024)
Economic empowerment is carried out to encourage, motivate and explore the potential of the community. That way, the condition of society will change from being helpless to being empowered. These empowerment efforts require support from various parties. Among them are the government and also non-governmental organizations. There is a goal of community economic empowerment that needs to be known, namely for the community to increase their income, solve the problems they face, and develop a system for accessing the necessary resources. The goal of community economic empowerment is to improve a community's quality of life, independence, and prosperity by addressing a variety of issues within that community. By granting more equitable access to financial resources and commercial possibilities, economic empowerment can contribute to the reduction of economic inequality. This study conducted an exploratory evaluation of the literature using a qualitative descriptive approach. Techniques for library research are used in the data collection process. This research discusses the definition and scope of economic empowerment, theories related to economic empowerment, economic empowerment policies, challenges and obstacles in implementing economic empowerment policies.